As I Remember: Stanton Gray (1967)
George P. Cooper's interview with Stanton Gray, who served as a member of the Agriculture Department faculty at Cal Poly from 1940 to 1941, and 1946-1960. [00:00:19] As I Remember Intro [00:00:36] Gray discusses his first contact with Cal Poly during the first summer session in 1931 [00:01:20] Gray recalls his first visit to Cal Poly [00:01:40] Gray recalls his honeymoon while he went to school [00:02:15] Gray describes coming from Hamilton City to Corning(?) [00:02:24] Gray recalls his role in the California Agriculture Teacher's Association [00:02:54] Gray recalls his preparation for becoming an agriculture teacher [00:03:30] Gray describes his experience at San Dimas [00:04:50] Gray recalls planting an orchard at Cal Poly [00:05:26] Gray recalls other faculty members during his time [00:06:47] Gray describes the opportunity he had to bring his students to the Los Angeles fruit market [00:07:18] Gray recalls becoming director of agriculture at Yuba(?) City High School [00:08:25] Gray describes working with Mexican nationals [00:09:33] Gray recalls what brought him back to Cal Poly in 1946 [00:10:15] Gray recalls what he had to learn upon arriving at Cal Poly [00:11:57] Gray describes running the store where Cal Poly products could be purchased [00:13:05] Gray describes the facilities of the agriculture department, such as an irrigation system, a field unit, and classrooms [00:13:31] Gray recalls working with international students [00:14:42] Gray describes his experiences when he was part of faculty and clubs [00:16:33] Gray recalls his participation in the summer conference of the Agriculture Teachers of America [00:17:36] Gray recalls his role in Future Farmers of America [00:18:38] Gray describes the differences between teaching college students and high school students [00:19:26] Gray describes the motivation of Cal Poly students [00:19:59] Gray recalls the increase in his workload as the agricultural department grew [00:20:33] Gray describes his role as adviser in crops club [00:21:25] Gray attributes his accomplishments to his wife [00:22:11] As I Remember Closing